Revisiting iron nutrition: a nano–organic approach for enhanced wheat yield, antioxidant resilience, and photosynthetic pigments - Hafiz Muhammad Jhanzab; Farhat Yasmeen; Ayshah Aysh Alrashidi; Muhammad Tanveer Altaf; Riaz Ahmad; Mohamed Ebaid; Ammar AL-Farga (Cereal Research Communications, 2026)

Harnessing biostimulants to alleviate potentially toxic element stress in vegetable crops - Amna Jamil; Waqas Liaqat; Asia Maqbool; Pramod Sargar; Muhammad Anwar-Ul-Haq; Shraddha Samindre; Muhammad Faheem Jan; Faheem Shehzad Baloch; Heba I. Mohamed; Muhammad Tanveer Altaf (Planta, 2026)

Elicitors in Plant Defense: Exploring Their Role in Biotic and Abiotic Stress Resistance - Muhammad Tanveer Altaf; Waqas Liaqat; Muhammad Aneeq Ur Rahman; Chidera Anuforo; Asia Maqbool; Amjad Ali; Muhammad Faheem Jan; Muhammad aasim; Heba I. Mohamed; Faheem Shehzad Baloch (Journal of Plant Growth Regulation, 2026)

Genetic Diversity and Population Structure of 72 Turkish Ficus carica (L.) Genotypes Assessed Using SCoT Markers - Meliha Feryal Sarıkaya; Muhammad Azhar Nadeem; Sarmad Ali Qureshi; Mehmet Bedir; Muhammed Tatar; Amjad Ali; Muhammad Tanveer Altaf; Viyan Acar Uçer; Kağan Kökten; Erdal Aglar; Faheem Shehzad Baloch (Biochemical Genetics, 2026)

Nanoparticles in Vegetable Production: From Soil to Human Health - Amna Jamil; Muhammad Tanveer Altaf; Ishtiaq Ahmad; Waqas Liaqat; Asia Maqbool; Muhammad Anwar-Ul-Haq; Pramod Sargar; Heba I. Mohamed; Faheem Shehzad Baloch (Water, Air, & Soil Pollution, 2026)

From global challenges to specific solutions: climate change impacts on agriculture with a focus on sorghum through bibliometric analysis - Waqas Liaqat; Muhammad Tanveer Altaf; Muhammad Faheem Jan; Haseeb Ahmad; Ehtisham Hassan Khan; Celaleddin Barutçular; Gönül Cömertpay; Faheem Shehzad Baloch; Heba I. Mohamed (Cereal Research Communications, 2025)

Endophytic fungi as biocontrol agents: A metabolite-driven approach to crop protection and sustainable agriculture - Muhammad Faiq; Amjad Ali; Shazia Shafique; Sobiya Shafique; Allah Rakha Yaseen; Rimsha Fatima; Muhammad Tanveer Altaf; Faheem Shehzad Baloch (Physiological and Molecular Plant Pathology, 2025)

Next-generation strategies for nitrogen-efficient maize production for a greener tomorrow - Muhammad Faheem Jan; Waqas Liaqat; Muhammad Tanveer Altaf; Muhammad Dawood Ahmadzai; Asia Maqbool; Faheem Shehzad Baloch; Ming Li (Field Crops Research, 2025)

Approaches for the amelioration of adverse effects of drought stress on soybean plants: from physiological responses to agronomical, molecular, and cutting-edge technologies - Muhammad Faheem Jan; Muhammad Tanveer Altaf; Waqas Liaqat; Changzhuang Liu; Heba I. Mohamed; Ming Li (Plant and Soil, 2025)

Genome-wide analysis of the UFGT gene family in colored cotton: evolution, structure and expression patterns - Jaweria Iqbal; Muhammad Tanveer Altaf; Waqas Malik; Abdul Qayyum (Genetic Resources and Crop Evolution, 2025)

Exploring genetic diversity of Turkish fig (Ficus carica L.) germplasm using inter-Primer Binding Site (iPBS) retrotransposon markers - Viyan Acar Uçer; Erdal Aglar; Parnaz Mortazavi; Sarmad Ali Qureshi; Amjad Ali; Muhammed Tatar; Muhammad Tanveer Altaf; Mehmet Bedir; Sezai Ercişli; Muhammad Azhar Nadeem; Faheem Shehzad Baloch (Genetic Resources and Crop Evolution, 2025)

Chlorophyll fluorescence: a smart tool for maize improvement - Muhammad Faheem Jan; Ming Li; Waqas Liaqat; Muhammad Tanveer Altaf; Changzhuang Liu; Haseeb Ahmad; Ehtisham Hassan Khan; Zain Ali; Celaleddin Barutçular; Heba I. Mohamed (Cereal Research Communications, 2025)

Advancing Chickpea Breeding: Omics Insights for Targeted Abiotic Stress Mitigation and Genetic Enhancement - Muhammad Tanveer Altaf; Waqas Liaqat; Amjad Ali; Amna Jamil; Muhammad Fahad; Muhammad Aneeq Ur Rahman; Faheem Shehzad Baloch; Heba I. Mohamed (Biochemical Genetics, 2025)

Molecular screening of diverse Tomato germplasm for root-knot nematode resistance using the Mi23 marker - Parnaz Mortazavi; Amjad Ali; Muhammed Tatar; Fatih Ölmez; Muhammad Tanveer Altaf; Muhammad Azhar Nadeem; Hayriye Yildiz Dasgan; Boran Ikiz; Tuğçe Temtek; Ömer Faruk Bilgin; Ayşe Mücahitoğlu; Mahmut Bayram; et al. (Physiological and Molecular Plant Pathology, 2025)

Development of tetraploids in tissue culture: modern techniques and biotechnological innovations - Sabeen Rehman Soomro; Salma Naimatullha Soomro; Muhammad Tanveer Altaf; Waqas Liaqat; Muhammad Azhar Nadeem; Faheem Shehzad Baloch; Muhammad Aasim; Heba I. Mohamed (Plant Cell, Tissue and Organ Culture (PCTOC), 2025)

Applicability of Start Codon Targeted (SCoT) markers for the assessment of genetic diversity in bread wheat germplasm - Muhammad Tanveer Altaf; Muhammad Azhar Nadeem; Amjad Ali; Waqas Liaqat; Mehmet Bedir; Nurettin Baran; Aleksandra Ilić; Muhammad Kashif Ilyas; Abdul Ghafoor; Hamide Dogan; Muhammad Aasim; Faheem Shehzad Baloch (Genetic Resources and Crop Evolution, 2025)
Research endeavors focused on examining genetic diversity play a pivotal role in advancing agricultural practices, as they furnish valuable insights for breeding programs and the preservation of germplasm. Wheat holds significant global importance as a cereal crop, serving as a primary source of sustenance for almost one-third of the global human population. In the current study, a total of 80 bread wheat genotypes were characterized using the start codon targeted (SCoT) marker system. A set of 14 polymorphic primers yielded a cumulative count of 399 bands with an average of 28.05 bands per primer. The range of diversity markers, such as polymorphism information content (0.26–0.59), effective numbers of alleles (1.27–1.59), Shannon’s information index (0.30–0.51), and gene diversity (0.18–0.34), provided evidence of elevated genetic differences within the examined germplasm. According to the findings of the molecular variance analysis, greater genetic variations are found within populations (92%). The model-based structural approach partitioned the 80 bread wheat genotypes into two distinct populations (Population A and B). The diversity indices based on the structures of the populations revealed that population A had greater diversity compared to population B. Both the principal coordinate analysis and the neighbor-joining analysis also differentiated the 80 different bread wheat genotypes based on their respective collection points. The present crop diversity offers great opportunities for enhancing crop quality and increasing tolerance to environmental challenges, both of which will lead to a reduction in the problem of food insecurity.

Applicability of SCoT markers in unraveling genetic variation and population structure among sugar beet (Beta vulgaris L.) germplasm - Nazlı Aybar Yalinkiliç; Sema Başbağ; Muhammad Tanveer Altaf; Amjad Ali; Muhammad Azhar Nadeem; Faheem Shehzad Baloch (Molecular Biology Reports, 2024)

In Silico Identification and Characterization of Rare Cold Inducible 2 (RCI2) Gene Family in Cotton - Muhammad Fahad; Leeza Tariq; Muhammad Tanveer Altaf; Muhammad Shahnawaz; Mudassir Aslam; Waqas Liaqat; Inayat Ullah; Izhar Ullah; Heba I. Mohamed; Abdul Basit (Biochemical Genetics, 2024)

Strategies and bibliometric analysis of legumes biofortification to address malnutrition - Muhammad Tanveer Altaf; Waqas Liaqat; Amna Jamil; Muhammad Faheem Jan; Faheem Shehzad Baloch; Celaleddin Barutçular; Muhammad Azhar Nadeem; Heba I. Mohamed (Planta, 2024)

A Bibliometric Analysis of Genome-wide Association Study (GWAS) and Sorghum (Sorghum bicolor L) Based on Web of Science Using VOS Viewer - Muhammad Tanveer Altaf; Waqas Liaqat; Amna Jamil; Muhammad Faheem Jan; Faheem Shehzad Baloch; Heba I. Mohamed (Journal of Soil Science and Plant Nutrition, 2024)

A Critical Review: Breeding Objectives, Genomic Resources, and Marker-Assisted Methods in Sorghum (Sorghum bicolor L.) - Muhammad Tanveer Altaf; Waqas Liaqat; Amna Jamil; Heba I. Mohamed; Muhammad Fahad; Muhammad Faheem Jan; Faheem Shehzad Baloch (Journal of Soil Science and Plant Nutrition, 2024)

Drought stress in sorghum: physiological tools, breeding technology, Omics approaches and Genomic-assisted breeding -A review - Waqas Liaqat; Muhammad Tanveer Altaf; Celaleddin Barutçular; Heba I. Mohamed; Zain Ali; Muhammad Owais Khan (Journal of Soil Science and Plant Nutrition, 2024)

Biochar: Black Gold for Sustainable Agriculture and Fortification Against Plant Pathogens—A Review - Usman Arshad; Muhammad Tanveer Altaf; Waqas Liaqat; Muhammad Ali; Muhammad Nadeem Shah; Muhammad Jabran; Muhammad Amjad Ali (Journal of Crop Health, 2024)

Sorghum: a Star Crop to Combat Abiotic Stresses, Food Insecurity, and Hunger Under a Changing Climate: a Review - Waqas Liaqat; Muhammad Tanveer Altaf; Celaleddin Barutçular; Heba I. Mohamed; Haseeb Ahmad; Muhammad Faheem Jan; Ehtisham Hassan Khan (Journal of Soil Science and Plant Nutrition, 2024)

Ultraviolet-B radiation in relation to agriculture in the context of climate change: a review - Waqas Liaqat; Muhammad Tanveer Altaf; Celaleddin Barutçular; Hira Nawaz; Izhar Ullah; Abdul Basit; Heba I. Mohamed (Cereal Research Communications, 2024)

iPBS-retrotransposons variations: DNA fingerprinting and the evaluation of genetic diversity and population structure in international cowpea germplasm - Faheem Shehzad Baloch; Muhammad Tanveer Altaf; Mehmet Bedir; Muhammad Azhar Nadeem; Muhammed Tatar; Tolga Karaköy; Muhammad Aasim (Genetic Resources and Crop Evolution, 2023)

Artificial neural network and decision tree facilitated prediction and validation of cytokinin-auxin induced in vitro organogenesis of sorghum (Sorghum bicolor L.) - Muhammad Aasim; Seyid Amjad Ali; Muhammad Tanveer Altaf; Amjad Ali; Muhammad Azhar Nadeem; Faheem Shahzad Baloch (Plant Cell, Tissue and Organ Culture (PCTOC), 2023)

Exploring the genetic diversity and population structure of upland cotton germplasm by iPBS-retrotransposons markers - Nurettin Baran; Flavien Shimira; Muhammad Azhar nadeem; Muhammad Tanveer altaf; Mehtap andirman; Faheem Shehzad Baloch; Mefhar Gültekin Temiz (Molecular Biology Reports, 2023)

Functional characterization of transcriptional activator gene SIARRI in tomato reveals its role in fruit growth and ripening - Muhammad Fahad; Muhammad Tanveer Altaf; Amna Jamil; Abdul Basit; Muhammad Mudassir Aslam; Waqas Liaqat; Muhammad Nadeem Shah; Izhar Ullah; Heba I. Mohamed (Transgenic Research, 2023)

Assessment of genetic diversity among 131 safflower (Carthamus tinctorius L.) accessions using peroxidase gene polymorphism (POGP) markers - Mehtap Yildiz; Muhammad Tanveer Altaf; Faheem Shehzad Baloch; Metin Koçak; Gökhan Sadık; Cansu Kuzğun; Muhammad Azhar Nadeem; Fawad Ali; Mehmet Bedir; Murat Tunçtürk (Molecular Biology Reports, 2022)

Applicability of inter-primer binding site iPBS- retrotransposon marker system for the assessment of genetic diversity and population structure of Peruvian rosewood (Aniba rosaeodora Ducke) germplasm - Faheem Shehzad Baloch; Stalin Juan Vasquez Guizado; Muhammad Tanveer Altaf; Ilker Yüce; Yeter Çilesiz; Mehmet Bedir; Muhammad Azhar Nadeem; Rustu Hatipoglu; Juan Carlos Castro Gómez (Molecular Biology Reports, 2022)